Effects of probiotics (Lactobacillus acidophilus) on liver functions in experimental colitis in rats: Majida A.J. al-Qayim and Delal Ebraheem Abass - al-Qayim, Majida A.J. (The Iraqi Journal of Veterinary Medicine, 2014)
The ameliorative effects of probiotics (Lactobacillus acidophilus) on liver functions in experimentally induced colitis in adult male rats were studied. Thirty six male rats divided randomly into 4 groups, 9 animals per group. First group considered as control (C-), 2nd group (T1) and 3rd group (T2) received (5 × 108 CFU) of Lactobacillus acidophilus as probiotics for 2 weeks by oral gavages needle, 4th group considered as colitis group (T3). Experimentally acetic acid colitis induced for rat of groups T2 and T3. After 7 days of colitis, at the end of the experiment. Blood sample, 4-5 ml, was collected via cardiac puncture for biochemical analysis and liver sections were isolated for histopathological examination. Results revealed that colitis caused significant (p<0.05) decrease in liver function enzymes AST; AST; ALP and FBS. While Lactobacillus acidophilus recipient succeeded in keeping ALP, FBS, and plasma total protein values within normal, but decreased ALT and AST in coparasim with control group. Histopathological liver section examination showed presence of focal necrosis in acetic acid colitis groups (T2 and T3), also these changes were prevented in liver sections of rats received Lactobacillus acidophilus confirmed the ameliorative effects of probiotics on hepatocellular, preventing hepatocellular damage in experimentally induced colitis.